Hubungan Antara Strategi, Sistem Pengendalian Manajemen dan Sistem Pengukuran Kinerja: Sebuah Studi Literatur - Wahyu Widarjo (Riset Manajemen dan Akuntansi, 2018)
This paper discusses the study results of the relationship between strategy, management control system and performance measurement system. Based on the literature review results, it can be concluded that there is a relationship between strategy, management control system, performance measurement system and organizational performance. Organizations need a strategy to achieve vision, mission and goals of organization. In the process of formulating strategy, organizations need to pay attention to strategic capabilities and resources, business environment or level of competition and capital structure. Furthermore, in the process of implementing strategy, a system is needed which can be used to ensure that the organization has implemented a strategy in line with the organization objectives. Therefore, control system and performance measurement system are needed which are synergistic or in line with the established strategy so that the organization can continue in innovating and it will enhance capability and competitiveness which will ultimately improve organizational performance. Keywords: Strategy, management control system, performance measurement system.